Filtration Process Optimization: Rheological Behavior of a Filter Cake at Different Moisture Contents. Issue 3 (29th January 2016) - Bourcier, Damien; Kong, Yan Siong; Feraud, Jean‐Pierre; Ode, Denis; Colson, Didier; Puel, François
Abstract: Transferring a wet cake from a filter to a dryer or furnace could severely lower the productivity of a whole process when the wet cake exhibits high viscosity and a sticky paste behavior. Depending on their moisture content, three distinct regions of rheological behavior were identified. Among them, only the granular solid type had sufficient flowability during the transfer operation. It was possible to discriminate the flow behavior more quantitatively by determining two transition values of moisture content. Rheological measurements were carried out at a constant shear rate representative of that encountered in the mechanical transfer system used at plant scale. The use of vane geometry for the rheometer was necessary to ensure an accurate repeatability of the viscosity measurements. Abstract : The transfer of a wet, highly viscous or sticky cake from filters to a dryer or furnace can significantly reduce the productivity of a whole process. Three distinct regions of rheological behavior were identified depending on the moisture content. A method is proposed to predict the transferability of a wet cake from a filter to a dryer or furnace that can be applied to any solid‐liquid system.